The Confused Path of the Australian Corporate Tax Residence Rules: Is Reform Necessary? - Allen, Christina (2024)
In 2020, the Board of Taxation submitted to the government a series of recommendations to reformulate the Australian corporate tax residence rules. The Coalition government proposed the the adoption of the main recommendations, but whether the current Labor government will implement the proposal remains uncertain. Considering several inconsistent reform options offered in Australian tax history, it is important to set out a primary goal for amending the corporate residence rules, if any. This article provides a survey of the operation of the corporate tax residence rules from the time that residence taxation was formalised in 1930 until now, including the latest High Court case in 'Bywater Investments Ltd v FCT', finding historical merit in the rules used as an instrument for source taxation. Australian courts have consistently applied the common law principle that assigns residence by reference to the superior authority or power to control a company's affairs, whereas various reform options have been suggested to provide definitional certainty in applying the central management and control test. Borrowing Marian's functional approach to examine the residence rules against the prevention of profit shifting and base erosion in source taxation, this article argues that the existing law is operating as intended. The only justifiable modification may be to provide that companies will no longer be Australian residents by reason of having their voting power controlled by Australian shareholders. This test has been used in a limited sense and appears to serve no apparent function.